O-012 The Intestinal Wound Regeneration Modulates Mucosal Microenvironment to Stimulate Expansion of a Local Pro-restitutive Microbiota. (March 2016) - Alam, Ashfaqul; Leoni, Giovanna; Quiros, Miguel; Wu, Huixia; Nusrat, Asma; Neish, Andrew
Abstract : Background: Ulcerative colitis and Crohn's disease frequently cause epithelial damage in the intestine, leading to gut inflammation accompanied by areas of ulceration. The regeneration of damaged mucosa as well as the restoration of intestinal homeostasis involve induced and coordinated proliferation and migration of intestinal epithelial cells. Commensal bacterial colonization of the intestine is essential for normal intestinal development, renewal, and repair. N-formyl peptide receptors (FPRs) are widely expressed pattern recognition receptors that can specifically bind and induce responses to host-derived and bacterial peptides and small molecules during repair of mucosal injury in a redox dependent manner. However, little is known about the host-microbiota crosstalk mediated by FPRs during repair of gut mucosal injuries. Herein, purpose of this study is to exploit the mechanism of mucosal healing promoted by a consortium of gut microbiota that preferentially colonizes ulcerated mucosa undergoing resealing. Methods: The regeneration of injured epithelial was studied using defined mechanical wounds inflicted in the mouse distal colon by employing a miniature endoscope and forceps. Microbiota studies were performed by high throughput sequencing of the V4 region of 16s rRNA gene of the bacteria harvested from mucosal wounds undergoing different stages of regenerative events. Results: The high throughput sequencing analysis of bacterial 16s rDNA determined rapid, reversible spatiotemporal alterations in the composition and diversity of microbiota in the wound microenvironment. Our data demonstrated that these ecological changes are dependent on FPR1/NOX2-mediated local tissue hypoxia, depletion of muc2 mucin, and compensatory effect of the over expression of HIF1-regulated MUC3 mucin. Our data show that these events of mucosal regeneration enrich a dominant member of this wound-associated consortium, Akkermansia muciniphila, which is associated with the pro-restitutive function. A. muciniphila, an anaerobic, mucinophilic commensal bacterium, enhanced proliferation and migration of enterocytes adjacent to the colonic wound beds in a process involving FPR1/NOX1 dependent redox signaling. Conclusions: These findings highlight a novel role of FPR1 to promote changes in the wound microenvironment to such extent that enriches a specific mucosa-associated bacterium to enhance enterocyte migration and proliferation in an FPR1-mediated and redox-dependent fashion.